(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Raja Rao is attrbured the following words in "The Future World is Bing made in America: By force of An Interview with Raja Rao": By force of circumstances purely accidental and aentmental’ I have lived abroad; my roots are in this country. That is why I come here every year and spend as much time as I can. I live abroad but I am chained to this country." One of the chains that bind Rao to India is his belief in the Indian Advanita,Vedanta philosophy. The Serpent and the rope can be read at different levels, and interpreted in different ways. The novelist has intertwined a number of ideas and themes in it. But the basic theme of the novel is that of metaphysical, quest. By metaphysic is meant the branch of philosophy that deals with the nature of existence, truth and knowledge. Raja Rao deals with the theme of self-knowledge, self-transcendence or self-fulfilment. The Serpent and the Rope is metaphysical insofar as it explores the nature of spiritual and metaphysical quest in some of its complex meanings, and attempts rare synthesis of the cultrures of Indian and Europe. Rao is in a propitious position to mediate between the two.